Fear of COVID-19 among pregnant women in Pakistan: a cross-sectional study - Nausheen, Sidrah; Bhamani, Shelia; Makhdoom, Areeba; Sheikh, Lumaan (International Journal Of Community Medicine And Public Health, 2020)
Background: The emergence of COVID-19 and its pandemic nature has exacerbated fears worldwide. Pregnant women are considered a vulnerable group during the COVID-19 pandemic because the physiological changes make them more susceptible to infections. Pregnant women are found expressing much of the fear related to their course of pregnancy, the in-utero transmission of the disease, and questions related to infection control in healthcare settings. Hence, the purpose of this paper was to explore the fears faced by pregnant women related to COVID. Methods: It was a cross-sectional survey among 201 pregnant women attending antenatal clinics of Aga Khan University Hospital. The survey tool contains demographic variables and a 7-item scale of “Fear in COVID” which is pre tested in the Iranian population. The survey form was made on google drive and sent to pregnant females on WhatsApp. Results: 201 pregnant women mostly belonging to middle and low socioeconomic class were enrolled. The majority (80%) of women were less than 30 years of age. Only 26 (12.9%) were primigravids, remaining were multigravidas of a different order of pregnancy. 60% of our study population showed high fear scores (27-35) from coronavirus whereas another 30% had moderate fear. No association of study variables was found with fear scores. Conclusions: We found a high level of fear of COVID-19 among the pregnant population with a higher level of anxiety and stress related symptoms. The amount of fear and stress is independent of the trimester or order of pregnancy.